Physicochemical Quality of Oyster Mushroom for Functional Food - Helmi Haris; Ridwan Rachmat; Tiana Fitrilia; Ahmad Syarbaini; Amar Ma’ruf; Dede Djuanda; Dian Histifarina; Bagem Sembiring (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
This article presents studies on the physicochemical quality of oyster mushrooms grown within a housing and controlled by the Internet of Things (IoT). The goals of this study were to assess (1) the impact of indoor air quality on the growth and quality of mushrooms and (2) the antioxidant content of oyster mushrooms. In this study, the air temperature and humidity of oyster mushroom house per unit time was recorded and controlled automatically by an IoT system. Additionally, their physicochemical and microbiological quality were evaluated using physico-analytical instruments, and the potency of their ergothioneine (EGT) content was investigated using the HPLC method. The temperature of the air inside was between 29 and 35 °C, and the relative humidity was between 60% and 90%. The average texture of mushroom is soft.  The average length, width, and height of the fresh mushroom were 41.5 mm, 60.0 mm, and 29.5 mm, respectively. The microbiological test confirmed that there was no salmonella infection in the collected mushrooms. The button-stage mushrooms have less total fungus than the bloom-stage mushrooms. The extraction standard method employs an EGT content of 0.674 mg/g as determined by chromatography data analysis. The oyster mushrooms can be consumed as a healthy meal, and the study of EGT showed also very prospective as one of immunotherapeutic food. Keywords: Ergothioneine, Fibre-reinforced plastic house, Internet of think, Oyster mushrooms